Comparison of the effectiveness of virtual reality-based education and conventional teaching methods in dental education: a systematic review - Hossain Koolivand; Mohammad Mahdi Shooreshi; Roya Safari-Faramani; Milad Borji; Meysam Siyah Mansoory; Hedaiat Moradpoor; Masoud Bahrami; Seyyed Mohsen Azizi (BMC Medical Education, 2024)
Abstract Background and objectives Virtual reality dental simulators as an educational tool may create specific training conditions for dental students, allowing them to practice dental skills in a safe and controlled condition. This study aimed to investigate the effectiveness of virtual reality-based education in dental education compared to traditional education approaches. Methods In this systematic review, four databases (PubMed, Scopus, Web of Science, and Science Direct) were searched until 2023 following PRISMA guidelines. The Quality assessment and risk of bias were assessed by the Cochrane Collaboration Tool for RCTs and GRADE, respectively. Inclusion criteria were restricted to randomized or quasi-randomized trials about virtual reality efficacy in dental education. Two authors independently evaluated the data and reviewed the overall risk of bias for all selected studies. Study design, sample size, hardware, onset time of intervention, duration, and number of procedures performed were among the data extracted. Results From the 703 titles, 48 full texts were chosen for review, yielding 14 articles for final inclusion. The review of these articles indicated the effective role of virtual reality dental simulators in improving students' knowledge and practical skills. Conclusions Based on our findings, adding haptic technology to virtual reality can improve students' practical skills, hand skills, theoretical knowledge, self-confidence, and learning environment. Although a fair amount of research needs to be done, notably on cost-effectiveness, student satisfaction, and other potentially adverse effects, virtual reality is a growing phenomenon with immense potential.